(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Janet’s Pares House Offers very reasonable and delicious native cuisine and has also won over its patrons’ hearts and taste senses in a similar fashion to the six major fast food chains. Additionally, it has been a top priority for the locals in the Novaliches region. Where can you find a flavorful lugaw worth less than ten pesos, and who can resist their pork and chicken barbeque and their sizzling sisig? Sulit-Sarap ka dito! It should be its appropriate characteristic. When customers pay for food, "Sulit" wants to make sure they get value for their hard-earned cash. A guarantee that their meals will be served by courteous and knowledgeable staff. The mission of "Sarap" is to provide a wide selection of delicious and high-quality products. In the Demographic profile of the respondents’ gender, most of the females always eat at Janet’s, and most Janet’s are those aged 26 and older, and they always visit weekly. In terms of service quality, Janet’s reliability has made most customers very satisfied with the products being served on time. And in tangibility, most of the customers are very satisfied with completely designed material such as menus. And the last is responsiveness. Most customers are very satisfied with responding to customers’ requests and complaints. In respondents’ descriptions of customer retention in food offerings, the customers are very satisfied with customer satisfaction with food service, and in customer service, the most satisfied customers are those who listen to their feedback and complaints, and in ambiance, the most satisfied customers are those who are satisfied with the physical environment of a restaurant. The company’s reliability, tangibility, and responsiveness should be improved in order to increase customer retention. And improve their food offerings to ensure customer satisfaction. To be able to retain Janet’s customers, researchers would like to recommend a strategy that can improve their business for better satisfaction and retention. In business, it is a must to listen to the customer, be patient, and be understanding to help you communicate effectively with the customer. Likewise, businesses need to improve their usability when providing products and services. To meet customer retention goals, they need to improve the quality of their customer service to improve customer satisfaction.